Role of Basti in Artavshaya w.s.r. to Lean and Obese Polycystic Ovarian Syndrome (AYUSHDHARA, 2024)
Polycystic ovarian syndrome is common endocrine, metabolic and lifestyle disorder for female reproductive age. Women with PCOS may not ovulate, have high level of androgens and have multiple cysts in the ovaries. PCOS can cause absent or irregular menstrual periods, excess hair growth, acne, infertility and weight gain. In Ayurveda, it can be correlated with Artavakshaya and Pushpaghani Jatharini. In the event of deficiency or loss of Artava, the menstruation does not appear in its appropriate time or is delayed (intermenstrual period is prolonged), is scanty and does not last for three days. There is also pain in vagina. This pain is due to aggression of Vayu caused by loss of Artava which fills this region, in modern context the treatment is based on hormonal preparation only which have may hazardous effect like weight gain, cysts in reproductive organ and chances of OHSS (ovarian hyper stimulation syndrome) and carcinoma. PCOS has two phenotypes, overweight/obese and lean, the latter being a much less common presentation of the syndrome. Lekhana Basti as a form of Niruha Basti which possesses Shodhana and Lekhana properties. Lekhana means scraping or scratching, this property helps to eliminate morbid Dosha and Lekhniya dravya removed increased Mala by their scraping action. PCOS is considered under Yonivyapad and Artava Dusthi and this Yoniroga cannot occur without vitiation of Vata dosha for this in Ayurveda, Basti (medicated enema) is the best therapy along with oral medications, in this article, we want to focus mainly on Basti therapy for both lean and obese PCOS, as customized approach.